Marital Future Anxiety (MFA) and its Relation to Self-Esteem Among a Sample of University Students - Aljundi , Nabil; Dasouqi, Doaa (Jordan Journal of Educational Sciences, 2017)
This study aims to identify the level of marital future anxiety (MFA) and its relation to self-esteem among university students in Hebron district, as well as to examine the differences in marital future anxiety according to some independent variables such as gender, economic status, place of residence, student’s academic level, and specialization. A random sample of (180) students spread over all of Hebron University, the Polytechnic University and the Al-Quds Open University was selected to participate in the study. The researchers used the descriptive approach, and both of the Marital Future Anxiety scale and the Rosenberg self-esteem scale were administered to respond on the research questions. The study revealed significant differences in the level of MFA due to gender in favor of females, due to place of residence in favor of city residents, due to the type of university in favor of Al-Quds Open University, and due to economic level in favor of low-income, while there were no differences due to specialization. The study recommended a set of recommendations, including: the need to educate young people about MFA concerns, and to promote social solidarity concepts in Palestinian society